DANCING WITH A BEAR: ONE UNIVERSITY’S EXPERIENCE WITH EVALUATING BLENDED LEARNING - Moskal, Patsy (Online Learning, 2009)
The 2008 Sloan Blended Workshop evaluation track provided participants with ideas, methods, and resources with which to design and evaluate their courses, programs, and blended initiatives. The many questions that arose from participants at the Workshop provided the motivation to document our University’s evaluation experiences at course, program and institutional levels. This paper presents our lessons learned including successes and challenges, with developing and conducting a longitudinal impact evaluation.